Political parties in the republican era (1958-1968) a comparative historical study (Journal of the College of Basic Education, 2022)
The period (1958 - 1968) was marked by political conflicts، and this conflict gave great importance to the emergence of political thought، but it did not have much importance، as the history of Iraq occupied an important and full center in the emergence of political and intellectual currents that played an important role in the instability of the situation in Iraq Parties were the product of and affected by society and thus affect the general conditions .